A development and implementation of a preconception counseling program for black women and men in the southeastern United States: a pilot protocol - Hernandez-Green, Natalie; Haiman, Madison D.; McDonald, Adenike; Rollins, Latrice; Farinu, Oluyemi T. O.; Clarke, Lasha S.; Huebshmann, Amy; Fort, Meredith P.; Chandler, Rasheeta D.; Brocke, Phebe; McLaurin-Glass, Danette; Harris, Erin; et al. (Frontiers in Public Health, 2024)
Introduction Racial/ethnic disparities in maternal mortality rates represent one of the most significant areas of disparities amongst all conventional population perinatal health measures in the U.S. The alarming trends and persistent disparities of outcomes by race/ethnicity and geographic location reinforce the need to focus on ensuring quality and safety of maternity care for all women. Despite complex multilevel factors impacting maternal mortality and morbidity, there are evidence-based interventions that, when facilitated consistently and properly, are known to improve the health of mothers before, during and after pregnancy. The objective of this project is to test implementation of pre-conception counseling with father involvement in community-based settings to improve cardiovascular health outcomes before and during pregnancy in southeastern United States. Methods and analysis This study has two components: a comprehensive needs and assets assessment and a small-scale pilot study. We will conduct a community informed needs and assets assessment with our diverse stakeholders to identify opportunities and barriers to preconception counseling as well as develop a stakeholder-informed implementation plan. Next, we will use the implementation plan to pilot preconception counseling with father involvement in community-based settings. Finally, we will critically assess the context, identify potential barriers and facilitators, and iteratively adapt the way preconception counseling can be implemented in diverse settings. Results of this research will support future research focused on identifying barriers and opportunities for scalable and sustainable public health approaches to implementing evidence-based strategies that reduce maternal morbidity and mortality in the southeastern United States’ vulnerable communities. Discussion Findings will demonstrate that preconception counseling can be implemented in community health settings in the southeastern United States. Furthermore, this study will build the capacity of community-based organizations in addressing the preconception health of their clients. We plan for this pilot to inform a larger scaled-up clinical trial across community health settings in multiple southeastern states.